STABILITY AND MECHANICAL PROPERTIES OF {AxA′(1-x)}{ByB′(1-y)}O3 CERAMICS - Akgenc, B.; Tasseven, C.; Cagin, T. (WILEY-BLACKWELL, 2015)
ABO(3) ceramics and their alloys form the basis of piezoelectricity based energy harvesting, actuators and electromechanical sensing for material health monitoring. Enhancing their electromechanical response is crucial for these technological applications. In this study we investigate the phase stability, anisotropic mechanical properties of various {A(x)A'((1-x))}{ByB'((1-y))}O-3 alloys using ab-initio density functional theory methods. The effects of composition, order on structure, energetics, elastic stiffness tensors are systematically investigated within the generalized-gradient approximation for A, A'=-Ba, Sr, Pb, K, Ag; B, B'=Ti, Zr, Nb using super cells with 2x2x2 unit cells, unite cubic phase. In the present work, we have used Linear Response Theory as well as homogeneous field methods to provide an assessment of the performance of these methods for determination of properties.
Keywords: First-principle calculations; Elastic constants; BaTiO3 crystals; ELASTIC PROPERTIES; PHASE-TRANSITIONS; X-RAY; SRTIO3; BATIO3; PBTIO3; BAZRO3; AGNBO3; Energy & Fuels; Engineering; Materials Science